The Role of social media And Destination Image on Visiting Decision: A Case Study in Taman Mini Indonesia Indah - Rully Arifiansyah; Darwin Raja Unggul Saragih (Budapest International Research and Critics University, 2022)
Social media as an online communication has been utilized by tourism organizer to become one of the promotional media, as well as a means of increasing attachment relationships with the community. The purpose of this study is to find out the role of social media in Taman Mini Indonesia Indah on tourist Visit Decision. The data was taken from 207 respondents of social media users. The research instrument used questionnaires through a number of items with a Likert scale of 1-5. And data processing uses the help of PLS consisting of Validity Test and Reliability Test. The data analysis in this study used Convergent Validity and Discriminant Validity. Structural Model Testing consists of R-square analysis with Blindfolding calculations. The results showed that the quality of destinations and the image of destinations had a positive and significant relationship, while social media had no significant effect on visiting decisions. This study highlights the use of social media is very important in an effort to improve the promotion of Taman Mini Indonesia Indah.